A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed